The Effect of Financial Leverage on Stock Return with Moderation of Corporate Social Responsibility Disclosure - Hermayani, Eka; Afandy, Chairil (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This research aims to assess how financial leverage affects stock returns while taking into account CSR disclosure as moderation. The research data were analyzed using panel data analysis. Secondary data in the study were taken from the 2013-2022 annual reports of banks listed on the Indonesia Stock Exchange (BEI). To measure the level of corporate social responsibility disclosure, the reporting standards of the Global Reporting Initiative (GRI) available through the ESGI data site were used. Sample selection was conducted using purposive sampling technique, which is a method that selects samples based on certain criteria relevant to the research objectives, and only samples that meet these criteria are used in the analysis. Data analysis using eviews12 which includes descriptive statistics, chow test analysis, classical assumption test, and equation (hypothesis testing). The research findings show that, when measured by the DER indicator, financial leverage significantly effects stock returns. However, if the DAR indicator is used to measure financial leverage, stock returns will decrease or have a negative effect. CSR disclosure moderateskthe effect ffinancial leverage on stock returns, if financial leverage uses the DER indicator in its measurement. However, CSR disclosure is not able to moderate the effect of financial leverage on stock returns if financial leverage uses DAR in its measurement. This study has several limitations, including a limited focus on the banking sector. In addition, the measurement of CSR disclosure is not based on specific criteria, but is adjusted to the disclosure of each company.